Madness in Teleorman: Chaos and Order - Eda Bayrakcı (Selçuk Üniversitesi Edebiyat Fakültesi Dergisi, 2023)
Chaos theory has emerged as a controversial scientific theory in the world of physics contrasting with the settled Newtonian theory supporting that the world and the universe have determinist and linear characteristics working in a regular and predictable way in the basis of causalities. Chaos theory offers the new world non-linearity, unpredictability, Fractal geometry against Euclid geometry and dependence on initial conditions. This theory born in physics has caused an enormous impact on social sciences, as well. Literature as the close follower of up-to-date theories and movements cannot keep away itself from this new theory. Numerous studies have been carried out in the West to interpret literary texts from different aspects –thematically or structurally- based on Chaos theory. This article aims to analyze Caryl Churchill’s Mad Forest issuing the Romanian Revolution from a modernist and surrealist way via key terms of Chaos theory with respect to theme and structure. Thus, Chaos theory and its key terms will be defined and its applications on literature will be discussed from different perspectives. Finally, Mad Forest will be analyzed regarding some key elements such as order within disorder, nonlinearity and dependence on initial conditions presented by perspectives of Chaos theory.